Evaluación de indicadores ecológicos asociados a ecosistemas riparios en la unidad hidrográfica Jipiro de la Hoya de Loja - Morocho Gallardo, Sally Cristina (2024)
Riparian ecosystems are transition zones where the aquatic and terrestrial environments interact; they are sensitive areas that perform functions of great importance such as the filtration of pollutants. These ecosystems are being negatively affected, influencing the quality and stability of the river, erosion, etc. Therefore, the present study aims to evaluate ecological indicators in riparian ecosystems by characterizing the composition and floristic structure, as well as periphyton communities. Six rectangular sampling plots of 25 × 5 m were established in conserved and recovering areas, where individuals with DBH ≥ 5 cm were recorded. Importance value indexes (IVI), diversity and similarity were calculated. Five sun-exposed substrates were sampled in each plot to evaluate periphyton communities. For the preservation of the samples, 1 ml of Lugol's solution was used for each 100 ml of sample which was then analyzed in the laboratory. In the conserved area an abundance of 81 individuals was found in which the best represented family was Rubiaceae; while in the recovering area a total of 79 individuals were found in which the best represented families were Lorantaceae and Betulaceae. According to the Shannon-Wienner index, the two zones have a medium diversity with a value of 2.61 for the conserved and 2.58 for the recovering areas respectevely. The Sorensen coefficient indicated a similarity of 23.25% with a floristic difference of 76.75%. The species of the periphyton communities with the highest abundance were Cocconeis placentula with 353 individuals for the conserved area and Hannaea arcus with 2 025 for the recovering area. The Shannon-Wienner index for the periphyton communities shown a medium diversity of 2.73 for the conserved area and 2.03 for the recovering area. Sorensen's coefficient indicated a similarity of 40% with a floristic difference of 60%. The floristic ecological indicators and the analysis of periphyton communities provided an additional tool for assessing the status and health of riparian ecosystems.